Growth Defects in InGaN‐Based Multiple‐Quantum‐Shell Nanowires with Si‐Doped GaN Cap Layers and Tunnel Junctions. Issue 6 (23rd February 2022) - Okuno, Koji; Mizutani, Koichi; Iida, Kazuyoshi; Ohya, Masaki; Sone, Naoki; Lu, Weifang; Okuda, Renji; Miyamoto, Yoshiya; Ito, Kazuma; Kamiyama, Satoshi; Takeuchi, Tetsuya; Iwaya, Motoaki; et al.
Abstract : Herein, the growth mechanism and defect structure of GaN‐based nanowire multiple‐quantum‐shells (NW‐MQSs) with cap layers combining tunnel junctions and n‐GaN are investigated in detail. In the NW‐MQS structure, defect structures are formed in three regions: (i) From the c ‐plane active layer at the tip of NW because of the low crystal quality of the active layer. (ii) Basal‐plane stacking faults (BSFs) with partial dislocations (PDs) are generated from the m ‐planes of the NW‐MQSs; these defects are triggered by the silicon nitride (SiN x ) formed on the NW surface. While some defects terminate because of the half loop formed by the PDs along the lateral growth of cap layers, others terminate at the coalesced region of the cap layers grown from adjacent MQSs. (iii) Line defects due to low‐angle grain boundaries and planar defects due to the BSFs in region (ii) are formed in the region wherein cap layers coalesce. The defects reaching the surface of the cap layers predominantly depend on the number of defects generated from the c ‐plane active layers in region (i). The growth mode and propagation mechanism of such defects are associated, and a method for realizing optical devices based on the high‐quality NW‐MQS structures is discussed. Abstract : The growth mechanism and defect structure of gallium nitride (GaN)‐based nanowire multi‐quantum‐shells (NW‐MQSs) with cap layers combining tunnel junctions and n‐GaN are investigated. In the NW‐MQS structure, defect structures are formed in three regions. The growth mode and distribution of defects are associated, and a method for realizing optical devices based on the high‐quality NW‐MQS structures is discussed.